(3JGQjN GdeSYhOis - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3bGd GdeSYhOi hQCjJ ai HdGO SQfOjf hgj LRjI ef LRGFQ GdHMQ s
(3BNQgG (B:s
(3jfJgi CKfGA bhdg bGd bOeJ ecI HYO bJd YKeGf HNeSI CjGe s
(3bWYI CNQi ef faS GdfSNI GdJi HQbe (B2999 (3cs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B80s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs